Integrating human factors in the LNG industry in pursuit of zero harm goal - Cafirma, June Tejano (2015)
Safety Management Systems (SMS) have been the primary driver to ensure safety of personnel in the workplace and to achieve the goal of "Zero Harm", which majority of the Liquefied Natural Gas (LNG) operators embrace. However, people are still being seriously harmed in the workplace despite of stringent safety policies, rules, procedures and processes. This dissertation explores the integration of Human Factors (HF) with SMS to create a safer workplace and to achieve the Zero Harm goal. A comprehensive approach that encompassed the entire life cycle of an LNG facility, from its conceptualization, design, construction, to its operation and maintenance was taken. The analysis also focused on potential errors that humans may make from time to time, to minimise the consequences on harm to people, damage to assets, or polluting the environment. Due to the broadness of the subject area, this study focuses only the integration of HF and SMS in the design phase. The approach and results of this study may then be applied to the other phases of the life cycle. An in-depth review of current SMS, Incident Database and case studies was taken to identify HF issues leading and/or contributing to the incidents. It showed that up to 84% of identified root causes and accidents were attributed to Human Factors. In pursuit of the Zero Harm Goal, the implementation of a systematic approach in integrating HF and SMS into the entire Lifecycle of a new LNG facility eliminates or reduces the 84% related causes attributed to Human Factors and can potentially have a significant impact on achieving the Zero Harm Goal in the workplace and cost savings from injuries and retrofitting work. By early intervention to integrate the proposed model with each phase of the project's lifecycle, human performance is expected to improve, as the operators' specific needs with respect to the operation of the plant, equipment and systems would have been resolved.